Cultural Representation of Paedocracy in the Pedagogical and Literary Discourse on King Matt the First by Janusz Korczak - Krasuska-Betiuk, Marta (Pedagogika Społeczna Nova, 2025)
The text presents testimonies of the reception of Janusz Korczak’s most popular novel, King Matt the First (1922), on the basis of which Iwona Chmielewska prepared an original artistic project in the form of a visual story (iconotext) entitled How Hard It Is to Be a King (2018). The content of scholarly discourse on the original work and its intersemiotic translation was analysed. Testimonies of the work’s reception, recorded in publications published or produced by academics after 2000, i.e. in the 21st century, were selected. Hitherto, these two cultural texts were considered from the paedocentric, philosophical, didactic, critical or literary perspective. In the first part, the main lines of the pedagogical-literary interpretation are recapitulated. Emblematic images and motifs from both works – the originalnovel and the picture book – are scrutinised in the article as examples of the cultural representation of the child and childhood and, more specifically, of the representation of paedocracy, which can be treated as the seed of a novel way of thinking about children’s participation in the social world.